Pemberian MPASI pada Bayi Usia 6 Bulan Sesuai Standar Gizi Kemenkes - Shella Dhika Rahmawati; Ni Kadek Krisna Dwi Patrisia; Almita Ratu Rifanda; Sofia Mardiana; Friesca Persityara Agatha; Aulia Ayu Kusuma W (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2022)
Complementary breast milk food (MP ASI) is food that is easy for babies to consume and digest. MP ASI given must provide additional nutrition to meet the nutritional needs of a growing baby. Even though breast milk is the best food for babies, babies aged > 6 months need more vitamins, minerals, protein and carbohydrates. This high nutritional need cannot only be obtained from breast milk, but also requires additional complementary foods from breast milk. So, what are the benefits of giving MP ASI to babies? MP ASI makes babies have a more complete source of nutrition. Even though breast milk is the best food for babies, after the age of >6 years babies need more vitamins, minerals, proteins and carbohydrates. This high nutritional need cannot only be obtained from breast milk, but also requires additional complementary foods from breast milk. However, MP ASI ~ does not mean stopping breastfeeding because during the first year MP ASI is only a means to supplement breast milk. MP ASI makes the baby less dependent on consuming excess breast milk. Giving MP ASI aims to train and get the baby used to consuming food that contains nutrients. that his body needs as he ages. Apart from that, MP ASI also helps develop the baby's ability to chew and swallow food.